1990 Seoul International Art Festival : Works on Mulberry Paper. (Seoul : The National Museum of Contemporary Art, 1990)
Africano, Nicolas ; Appel, Karel ; Arman, Armand P. ; Baechler, Donald ; Baruchello, Gianfranco ; Bellegarde, Claude ; Benaim, Richardo ; Bertini, Gianni ; Brusse, Mark ; Buren, Daniel ; Chamberlain, John ; Charney, Melvin ; Chihuly, Dale ; Ciuha, Joze ; Downey, Juan ; Francis, Sam ; Farhi, Jean-Claude ; Frank, Mary ; Graves, Nancy ; Heske, Marianne ; Honegger, Gottfried ; Hundertwasser ; Hunt, Bryan ; Jaccard, Christian ; Jones, Allen ; Kabakov, Ilya ; Kantor, Tadeusz ; Karavan, Dani ; Kasten, Petra ; Kirkeby, Per ; etc.
1990 Seoul International Art Festival, The National Museum of Contemporary Art, Seoul, 21.11.1990 - 20.02.1991
boek